Prebreeding studies of leaf rust resistant Triticum aestivum/T. timopheevii line L624 - S. N. Sibikeev; I. G. Adonina; A. E. Druzhin; O. A. Baranova (Вавиловский журнал генетики и селекции, 2023)
Triticum timopheevii Zhuk. attracts the attention of bread wheat breeders with its high immunity to the leaf rust pathogen. However, introgressions from this species in Triticum aestivum L. are little used in practical breeding. In the presented study, the agronomic value of T. aestivum/T. timopheevii line L624 was studied in comparison with the parent cultivars Saratovskaya 68, Dobrynya and the standard cultivar Favorit during 2017–2022. Introgressions from T. timopheevii in L624 were detected by the FISH method with probes pSc119.2, pAs1 and Spelt1, as well as micro satellite markers Xgwm312, Xgpw4480 and Xksum73. Translocations of 2AS.2AL-2AtL and on 2DL were detected as well. Line L624 is highly resistant to Puccinia triticina both under the background of natural epiphytotics and under laboratory conditions. PCR analysis with the DNA marker of the LrTt1 gene (Xgwm312) revealed that it is not identical to the Lr gene(s) in L624. According to a five-year study, the grain yield of L624 was, on average, higher than that of Favorit and Dobrynya, but lower than that of Saratovskaya 68. Line L624 had a lower weight of 1000 grains than the recipients, and was at the same level with the standard cultivar Favorit. Introgressions from T. timopheevii in L624 increased the grain protein content by comparison with Saratovskaya 68 and Favorit, but it was at the same level as in Dobrynya. As for parameters of flour and bread, L624 was not inferior to the recipient cultivars, but by volume and porosity of bread, it surpassed Saratovskaya 68. Moreover, L624 surpassed Favorit by the elasticity of the dough, the ratio of the elas ticity of the dough to the extensibility and the strength of the flour. Thus, the results obtained suggest that introgressions in chromosomes 2A and 2D in L624 do not impair baking properties.